Social-psychological risk perception impacts on job insecurity and turnover intention: a mediation model using PLS-SEM technique - Ibrahim A. Elshaer (Cogent Psychology)
The tourism business has been greatly affected by the COVID-19 pandemic, leading to numerous challenges for tourism employees, particularly those in frontline positions who directly interact with customers (e.g. hotel employees). The pandemic has caused psychological and social risks, including fear of infection, job loss, and financial insecurity, which have affected employees’ intention to leave the job. This study aims to explore the psychological and social risk perceptions of front-line hotel employees post-COVID-19 and their impact on turnover intention (TI). Moreover, the study investigates the mediating role of job insecurity (JI) in the link between risk perception and TI. A quantitative research method, employing a survey questionnaire to collect the required data from hotel employees was conducted among 330 tourism employees. Data was evaluated using “partial least square structural equation modeling” (PLS-SEM). The findings indicate that tourism employees who perceive high levels of psychological and social risk have a higher intention to quit their jobs. Moreover, the perceived risk of job insecurity mediates the link between psychological and social risk perception and TI. The study provides insights for tourism organizations to identify and mitigate the risks that affect employees’ perceptions and retention. This study adds to the existing body of literature regarding the psychological and social effects of the COVID-19 pandemic on employees in the tourism sector. The study highlights the potential long-term implications for the financial stability of the tourism industry, considering the significant financial consequences associated with turnover intention and job insecurity amid the pandemic.